Teachers' Challenges in Implementing Differentiated Instruction in Teaching English at Junior High School - Imas Suryati; Koesoemo Ratih; Maryadi Maryadi (Eduvest - Journal of Universal Studies, 2023)
The objective of the study was to find out the teachers’challenges in implementing Differentiated Instruction in Teaching English at Junior High School. The subject in this study was an English teacher while the object was DI’ theory by Tomlinson. Qualitative phenomenology was the method and type of approach chosen in this study. This study used interview, observation, and analysis of documentation as instruments for collecting data. The data analysis techniques used in this study were data collection, data reduction, data display, and conclusions. The results of the study found that the implementation of differentiation based on content, process and product has been carried out properly as evidenced by teacher understanding, class observations and the existence of document used for teaching. Therefore the evaluation process was not only carried out on students but also in the learning process and the lesson plans used. The results for the challenges faced by teacher were time and effort in preparing and designing the learning process and lack of support from another teacher.